THE SPECIFICITY OF PHYSICAL TRAINING OF ATHLETES,I.E., FUTURE SPECIALISTS IN PHYSICAL CULTURE (Academicia Globe: Inderscience Research, 2023)
The article presents the results of the analysis of scientific and methodological literature, pedagogical observationand conversation.